The Concept of Voluntary Disclosure in The Tax Audit Process: A Preliminary Study in Indonesia - Nanda ALFIYANDI; Ning RAHAYU (Communications of International Proceedings, 2021)
This study discusses the basic differences between the alternative of disclosing untruth and alternative tax audit in terms of advantages and disadvantages. This study wants to describe and analyze the policy of disclosing untruth in the Tax Audit process in Indonesia and analyze the advantages and disadvantages between the mechanism for disclosing untruth or auditing by the DGT. In addition, this research will also describe the problems faced in its implementation in the field (especially in the disclosure of untruths). This research approach uses a qualitative approach and data collection in this study will be carried out through library research and field studies by conducting in-depth interviews with several key informants who are relevant stakeholders. The results of the study indicate that both mechanisms have advantages and disadvantages that can be taken into consideration by taxpayers. In the Job Creation Law and the Harmonization of Taxation Law, the government has made favorable rules for taxpayers who make voluntary disclosures.
Keywords: Voluntary Disclosure; Tax Audit; Tax Compliance.